2015
DOI: 10.1080/15592294.2015.1048412
|View full text |Cite
|
Sign up to set email alerts
|

Placental mitochondrial methylation and exposure to airborne particulate matter in the early life environment: An ENVIRONAGE birth cohort study

Abstract: Abbreviations: 12S rRNA, Mitochondrial ribosomal 12S rRNA; D-loop, Displacement loop; IQR, Interquartile range; mtDNA, Mitochondrial DNA; mtDNMT1, Mitochondrial isoform of nuclear-encoded DNA methyltransferase enzyme 1;MT-RNR1, Mitochondrial region RNR1; PM, Particulate matter.Most research to date has focused on epigenetic modifications in the nuclear genome, with little attention devoted to mitochondrial DNA (mtDNA). Placental mtDNA content has been shown to respond to environmental exposures that induce oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 45 publications
4
140
1
1
Order By: Relevance
“…Air pollution has been associated with negative pregnancy outcomes 284, 285, 287290, 293, 298, 299 , including low birth weight 292295, 302 , respiratory illnesses 301 and mortality 301, 303 in the fetus, newborn and infant. Increased in utero exposure to PM 2.5 , especially in the first trimester of pregnancy, is positively associated with placental mtDNA methylation (in both the displacement loop and the sequence which encodes the mitochondrial ribosomal 12S rRNA) 215 . Conversely, increased in utero exposure to PM 2.5 or PM 10 is negatively associated with mtDNA content with the most significant association in the third trimester 215, 216 .…”
Section: 5 Reproductive and Developmental Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…Air pollution has been associated with negative pregnancy outcomes 284, 285, 287290, 293, 298, 299 , including low birth weight 292295, 302 , respiratory illnesses 301 and mortality 301, 303 in the fetus, newborn and infant. Increased in utero exposure to PM 2.5 , especially in the first trimester of pregnancy, is positively associated with placental mtDNA methylation (in both the displacement loop and the sequence which encodes the mitochondrial ribosomal 12S rRNA) 215 . Conversely, increased in utero exposure to PM 2.5 or PM 10 is negatively associated with mtDNA content with the most significant association in the third trimester 215, 216 .…”
Section: 5 Reproductive and Developmental Effectsmentioning
confidence: 96%
“…PM has been shown to accumulate within the mitochondrion 212 and can disrupt mitochondrial membrane potential 214 , damage mitochondrial structure 212 , alter the mtDNA (strand breaks and methylation) 214,215217 , and activate the mitochondrial programmed apoptosis in pulmonary tissues. Exposure of murine macrophage and human bronchial epithelial cell lines to diesel exhaust particles suspended in the culture media resulted in a preferential accumulation of PM 0.1 within the mitochondrion 212 .…”
Section: 0 Toxicity Of Air Pollutionmentioning
confidence: 99%
“…Cord blood was separated into plasma and buffy coat by centrifugation and buffy coat was stored at -20°C. Placentas were sampled per a published protocol [11], immediately after birth. Each of four samples (∼1 cm 3 ) was taken on the fetal side approximately 4 cm from the cord insertion site and approximately 1-1.5 cm below the fetal membrane to avoid membrane contamination.…”
Section: Subject and Tissue Collectionmentioning
confidence: 99%
“…Another study showed differences in DNA methylation of the D-Loop and MT-RNR1 were concordant with methylation differences in the subtelomeric region D4Z4 in umbilical cord blood as well as the fetal and maternal side of the placenta, suggesting a potentially common epigenetic signature in these tissues [29]. The same group also recently demonstrated a positive correlation between airborne particulate matter exposure and placental mtDNA methylation in the D-Loop and MT-RNR1 using targeted bisulfite-pyrosequencing [30]. This study also showed that increased mtDNA methylation is accompanied by a reduction in mtDNA content, a potential marker of mitophagy, potentially indicating that alterations in mtDNA methylation of the D-Loop, a region highly involved in mtDNA transcription and replication, may lead to changes in mitochondrial biogenesis.…”
Section: Introductionmentioning
confidence: 95%
“…This is more pertinent to studies of mtDNA epigenetics than in studies of ncDNA methylation given the low levels of mtDNA methylation identified in recent studies [30, 49]. Currently, the only published genome-wide study investigating mtDNA methylation utilized publically-available methylated DNA immunoprecipitation sequencing (MeDIP-Seq) data [50].…”
Section: Introductionmentioning
confidence: 99%